Multistage targeted "Photoactive neutrophil" for enhancing synergistic photo-chemotherapy. (December 2021) - Xu, Yurui; Zhang, Xiaomin; Hu, Getian; Wu, Xiaotong; Nie, Yuanyuan; Wu, Heming; Kong, Desheng; Ning, Xinghai
Abstract: Cell-based drug delivery system holds a great promise in anticancer treatment, due to its potential of maximizing therapeutic efficacy while minimizing adverse effects. However, current cell system can only deliver drugs in tumor lesions, but lack an ability to target subcellular locus of therapeutic actions, thereby compromising anticancer efficacy. Herein, we bioengineered living neutrophils as a novel type of "Photoactive neutrophil" (PAN) with capabilities of self-amplified multistage targeting and inflammation response for enhancing mitochondria-specific photo-chemotherapy. PAN encapsulated multifunctional nanocomplex (RA/Ce6) of RGD-apoptotic peptide conjugate (RA) decorated liposomal photosensitizer Ce6, and could overcome tumor barriers to selectively release RA/Ce6 within tumor. Consequently, RA/Ce6 actively entered cancer cells and accumulated in mitochondria to trigger combined photodynamic therapy (PDT) and RA-induced mitochondrial membrane disruption, resulting in enhanced therapeutic effects. Importantly, PAN exhibited inflammation amplified tumor targeting after PDT, and initiated combined photo-chemotherapy to suppress tumor growth without adverse effects, leading to prolonged mice survival. Therefore, PAN represents the first multistage targeted cell therapy, and brings new insights into cancer treatment.